Covid-19 S Impact on Worker Stress in Human Service Organizations: The Mediating Role of Inclusion - Calderon-Orellana, M (Public Library of Science, 2023)
Human service organizations faced extraordinary challenges due to COVID-19. Despite the increasing interest and research in this new scenario, there has been limited discussion about the impact of COVID-19 on workers, the challenges they faced, and the resulting stress. This study aimed to analyze the impact of COVID-19 on work-related stress and the mediating role of inclusion among workers in human service organizations in Chile during the pandemic. The research design was quantitative and involved a sample of 173 workers from civil society organizations who were contacted during the pandemic. The study confirmed that individuals most affected by the pandemic experienced higher levels of workrelated stress, and that inclusion played a negative mediating role in this relationship. This article highlights the importance of relationships, decision-making processes, and access to information in reducing stress in post-COVID scenarios for organizations that traditionally handle crises. © 2023 Caldero´n-Orellana et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.